One health integrated approach to 21st century challenges to health - Prata, Joana C.; Ribeiro, Ana Isabel; Rocha-Santos,Teresa (Cambridge, Massachusetts Academic Press, 2022)
"One Health: Challenges for the 21st Century is a transdisciplinary approach to health, considering the interdependency of human, animal, and environmental health. This approach to health promotion and disease prevention calls for integrative and interdisciplinary cooperation. From zoonotic diseases to environmental degradation, this book introduces core concepts of the One Health approach by presenting focal key challenges. The objective of this book is not centered solely on epidemiologic interactions of infectious diseases but also on the environmental and ecological implications of current major threats. Written by international experts, the ten chapters provide a comprehensive approach consisting of core concepts, practical examples, and applications that align with key challenges to public health. Therefore, this book is a valuable resource for public health professionals, veterinarians, physicians, environmental researchers, policymakers, and other professionals who seek to understand the overarching complexities of health."
Includes bibliographical references and index.
Keywords: Environmental health; One Health; Public health; Zoonoses